Multidisciplinary Information Retrieval 7th Information Retrieval Facility Conference, IRFC 2014, Copenhagen, Denmark, November 10-12, 2014, Proceedings - Lamas, David; Buitelaar, Paul (Information Systems and Applications, incl. Internet/Web, and HCI, 2014)
This book constitutes the proceedings of the 7th International Information Retrieval Facility Conference, IRFC 2014, held in Copenhagen, Denmark, November 2014. The 10 papers presented together with one industry paper were carefully reviewed and selected from 13 submissions. The conference aims at bringing young researchers into contact with the industry at an early stage, emphasizing the applicability of IR solutions to real industry cases and the respective challenges.